Head pain in the competitive aquatic athlete-an approach to a differential diagnosis and management - Beduhn, B.; Roe, G.; Furst, W.; Lewno, A. (Current Sports Medicine Reports, 2022)
Aquatic athletes not only face common headache etiologies similar to the general population and land-based athletes but also experience their own unique pathology. Posture, aquatic pressure, equipment, and even marine animals pose as unique causes to head pain in the aquatic athlete. Common head pain pathologies seen in the aquatic athlete include tension-type headaches, migraines, cluster headaches, and compressive headaches, including supraorbital neuralgia. Creating a thorough but focused differential diagnosis for head pain in the aquatic athlete can be a difficult and overwhelming task for some. We review both the common and not-so-common etiologies of head pain in the aquatic athlete and suggest a simple framework for assessment and treatment to diagnose and treat head pain in this specific population.